Methicillin Resistant Staphylococcus aureus nasal carriage among apparently healthy University Students - Ahmed Olowo-okere 1* , Umar Maryam 1 , Mus’ab Ibrahim 1 , Habeebah Olufe Owolabi 1 , Adeiza Suleiman Shuaibu , Adeboye Olusoji Lekan , Mustapha Usman , Abdulmalik Aliyu , Larbi Zakaria Nabti , Abdourahmane Yacouba (Sokoto Journal of Medical Laboratory Science)
Medical and paramedical students are often exposed to MRSA colonization and infection during clinical postings. They may serve as reservoirs or vector and occasionally as victims of MRSA cross-contamination. This study was designed to determine the rate of MRSA nasal carriage among apparently healthy undergraduate medical students of Usmanu Danfodiyo University Sokoto. A questionnaire was administered to collect demographic data and health history of the recruited participants. Swab sticks pre-moistened with sterile physiological saline was used to collect samples from the nasal cavities of the participants. The collected samples were processed using standard microbiological techniques. The presence of MRSA was determined using the Oxacillin resistance screening agar base test (ORSAB). The susceptibility of the MRSA isolates to commonly prescribed antibiotics was carried out using the disc diffusion method. A total of 200 participants were recruited from medical and allied faculties. The participants comprised of 120 clinical students and 80 pre-clinical students. The mean age of the study participants was 23.32±1.76 years. Majority of the participants were males 119 (59.5 %). Overall, 77 (38.5 %) of the study participant were found to be nasally colonised with MRSA. The carrier rate was higher among the male (61.0 %) and participants aged less than 20 years (79.2 %). Equally, higher MRSA colonisation rate was observed among the students of faculties of medicine (27.3 %) and nursing (22.1 %) and predominantly among the clinical students (53.2 %). Clinical students and students who visited the hospital more than four time in a month were 0.72 (95% CI, 0.394-1.328) and 0.61 (95% CI, 0.325- 1.136) times more likely to carry MRSA, respectively. The MRSA isolates were highly 60 resistant to all the tested antibiotics (72-100 %). The MRSA nasal carriage rate among medical and paramedical students of Usmanu Danfodiyo University Sokoto is high. The finding of this study has important implication on public health. Thus, urgent steps should be taken to improve infection control practices in the study area.